2003
DOI: 10.1080/15428110308984825
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Exposure to Diesel Exhaust in the Canadian Federal Jurisdiction

Abstract: To assess the impact of the proposed American Conference of Governmental Industrial Hygienists threshold limit value-time-weighted average to diesel particulate matter (DPM), 177 full-shift samples were taken in 23 workplaces under Canadian federal jurisdiction. National Institute for Occupational Safety and Health (NIOSH) Method 5040 (Elemental Carbon: Diesel Exhaust) was used to assess exposure. Quality control tests were conducted prior to field sampling by taking air samples in the exhaust stream of two di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…Moreover, the surface reactivity of the stationary collected particles in these bus depots, described in a previous paper [27], indicated that PM 4 was quite oxidized, probably because of ageing. EC results (Table 2 stationary measurements) were comparable with those obtained in previous studies in bus depots [30,43,44]. Unlike PM 4 and OC, the concentrations of EC measured in personal air sampling (Table 2 personal measurements) were comparable to those measured using stationary air sampling.…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, the surface reactivity of the stationary collected particles in these bus depots, described in a previous paper [27], indicated that PM 4 was quite oxidized, probably because of ageing. EC results (Table 2 stationary measurements) were comparable with those obtained in previous studies in bus depots [30,43,44]. Unlike PM 4 and OC, the concentrations of EC measured in personal air sampling (Table 2 personal measurements) were comparable to those measured using stationary air sampling.…”
Section: Discussionsupporting
confidence: 87%
“…Table 5 presents the exposure levels to EC of other occupational groups measured using NIOSH method 5040. Compared with other studies, the MHW collectors (GM = 5.6 μg/m 3 ) were exposed to slightly higher levels than mechanics of truck repair garages (GM = 3.2–5.9 μg/m 3 ), mechanics of locomotive workshops (GM = 2.6–3.2 μg/m 3 ), truck drivers (GM = 1.1–4.0 μg/m 3 ), railroad crews (GM = 1.4–5.6 μg/m 3 ), and surface workers at mining facilities (GM = 1–4 μg/m 3 ) [ 18 , 20 , 31 , 33 37 ]. The exposures of MHW truck drivers (GM = 3.8 μg/m 3 ) were comparable to local truck drivers (GM = 1.2–4.0 μg/m 3 ) and long-haul truck drivers (GM = 1.1–3.8 μg/m 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since DPM is a mixture of various components, EC, OC, total carbon (TC, EC+OC), BC and fine particulate matter (PM 2.5) can be used to determine DPM exposures [ 17 19 ]. Among these, EC is known as the most useful marker of DPM because it is generated proportionally to DPM, relatively free of interferences (unlike OC), and can be measured at low concentrations [ 17 , 18 , 20 ]. BC (black aerosol, soot, carbonaceous aerosol) is often used interchangeably with EC, but the term was defined by measuring light-absorbing carbon.…”
Section: Introductionmentioning
confidence: 99%
“…Temperature and/or the amount of light transmitted through filters are used to split the OC from the more recalcitrant EC. In order to facilitate inter-laboratory comparison, the National Institute for Occupational Safety and Health (NIOSH) published Method 5040 (NIOSH, 1998) and since its publication, it has been widely used in environmental and health studies (Fromme et al , 2005; Seshagiri & Burton, 2003). …”
Section: Introductionmentioning
confidence: 99%